THE EXAMINATION OF EXPLOSIVE LEG STRENGTH IN VOLLEYBALL - Biróné Ilics, Katalin (Stadium - Hungarian Journal of Sport Sciences, 2024)
The goal of the volleyball game is for players to get the ball over the net to the opposite side, which they do by jumping up to score. The effectiveness of the jumps is mainly a function of the leg’s acceleration. This ability also appears in executing tasks following a deep center of gravity defense. Our study primarily aims to collect tests to measure the rapid strength of legs and predict expected performance. Furthermore, we evaluate the reliability of the tests by reviewing studies analyzing the vertical jump of volleyball players. We grouped the tests into two main categories. We have processed laboratory tests (e.g., force plate, contact mat) and their associated motion analysis software and court tests (e.g., standing long jump, wall touch method). Combining the two groups of tests is essential to obtain relevant results.